2018
DOI: 10.1021/jacs.8b07775
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation State Distributions Provide Insight into Parameters Directing the Assembly of Metal–Organic Nanocapsules

Abstract: Two structurally analogous Mn-seamed C-alkylpyrogallol[4]arene (PgC )-based metal-organic nanocapsules (MONCs) have been synthesized under similar reaction conditions and characterized by crystallographic, electrochemical, and magnetic susceptibility techniques. Both MONCs contain 24 Mn centers, but, somewhat surprisingly, marked differences in oxidation state distribution are observed upon analysis. One MONC contains exclusively Mn ions, while the other is a mixed-valence Mn/ Mn assembly. We propose that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19][20] Crystalline CAMs with large pores drew extraordinary attention owing to their promising guest-molecule encapsulation capacities, which demonstrate broad application prospect in chemical sensing, catalysis, drug delivery, and host-guest chemistry. [21][22][23][24][25][26] Although many research endeavors have focused on the development of new crystalline CAMs, it is unfortunate that those with large pores, high-porosity, and noninterpenetrated structures have rarely been reported, probably because constructing novel porous crystalline CAMs still present an enduring and significant challenge. Thus further detailed exploration of their properties and applications remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20] Crystalline CAMs with large pores drew extraordinary attention owing to their promising guest-molecule encapsulation capacities, which demonstrate broad application prospect in chemical sensing, catalysis, drug delivery, and host-guest chemistry. [21][22][23][24][25][26] Although many research endeavors have focused on the development of new crystalline CAMs, it is unfortunate that those with large pores, high-porosity, and noninterpenetrated structures have rarely been reported, probably because constructing novel porous crystalline CAMs still present an enduring and significant challenge. Thus further detailed exploration of their properties and applications remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…MONCs seamed by redox stable metal ions (for example, Zn II , Mg II , or Ga III ), are relatively easy to synthesize, while those constructed from redox-active metals are relatively difficult. [31][32][33]62 Previous works have demonstrated that the reaction of Mn II or Fe II with pyrogallol [4]arenes yields MONCs with metal ions in mixed valence. 31−33 The complicated coordination environment is not favorable to form CP-MONCs.…”
Section: Coordination Polymers Based On Hexameric Moncsmentioning
confidence: 99%
“…Metal–organic nanocapsules (MONCs) are self-assembled capsule-like nanostructures with permanent internal cavities and fantastic geometrical shapes. In particular, MONCs constructed with metal ions and bowl-shaped C- alkylpyrogallol­[4]­arenes (PgCs) have attracted great attention because of their unique and robust structures. , Twelve phenolic hydroxy groups on the upper rim of the PgC seam with appropriate metal ions result in the formation of hierarchical superstructures. To date, studies on PgC-assembled MONCs have been focused on the synthesis of capsules by employing various metal ions or control of the internal volume of the MONCs (i.e., dimeric and hexameric capsules). ,, Recently, a new discovery related to the modification of the exoligand on the surface of the MONCs is of great interest to us: these MONCs possess a large number of open metal sites on their exterior, making it facile to assemble MONCs into hierarchical coordination polymers. ,, Coordination polymers constructed from PgC-assembled MONCs (CP-MONCs) can be considered as another type of metal–organic framework (MOF) with higher complexity (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…The cone-shaped PgCn, which is the tetramer of the natural phenolic mimic pyrogallol (PG) with variable length sidechain groups (Figure 1c), has been demonstrated as a versatile precursor for construction of metal-organic nanocapsules. [24][25][26][27][28][29][30][31][32][33][34] Based on coordination assemblies of PgCn (n = 3, 5 or 9) with actinides ions, we have achieved high-performance uranyl capture via uranyl-PgCn nanocages (Figure 1d) assembled in situ in monophasic or biphasic solvent systems. This type of extraction as nanoscale species is unprecedented for actinide ions and it leads to a novel paradigm for hybrid nanocluster-based actinide sequestration, which may be considered as "nanoextraction".…”
mentioning
confidence: 99%